Long term trend in surface ozone over Indian stations (MAUSAM, 2016)
In this paper we have presented long term variation of surface ozone over more than two decades (1990-2013) simultaneously for three different cities, viz., Pune, New Delhi and Thiruvananthapuram. Surface ozone concentration has been measured at these cities continuously with the help of a continuous recorder using electrochemical sensor. The detailed study of annual trend, diurnal as well as seasonal behaviour of ozone has been carried out. Diurnal changes seen over 3 time periods, i.e., 1990-2000, 2000-2010 and 2010-2013 have also been analyzed in this study. Time series analysis during the observational period indicates that annual average concentration of ozone is increasing at all the three stations, i.e., Delhi, Pune and Thiruvananthapuram respectively. Average rate of increase is estimated to be 0.05, 0.04, 0.04 ppb per year for Delhi, Pune and Thiruvananthapuram respectively. The diurnal variation in ozone concentration in urban areas exhibits marked diurnal variability, with high concentrations during the day and low concentrations at night. Apart from the above diurnal change, day to day record shows a forenoon sharp increase, a characteristic feature of an urban site. An increase in surface ozone concentration is also observed from (1990-2000) to (2010-2013) at all the three locations. The amplitude of diurnal increase in surface ozone concentration from 1990 to 2013 as obtained is more for Delhi, i.e., 0.5 ppb per year, as compared to Pune and Thiruvananthapuram.